Hydrogen bonding and cooperativity in isolated and hydrated sugars: mannose, galactose, glucose, and lactose. - Carçabal, P; Jockusch, R; Hünig, I; Snoek, L; Kroemer, RT; Davis, B; Gamblin, D; Compagnon, I; Oomens, J; Simons, J (2005)
The conformation of phenyl-substituted monosaccharides (mannose, galactose, and glucose) and their singly hydrated complexes has been investigated in the gas phase by means of a combination of mass selected, conformer specific ultraviolet and infrared double resonance hole burning spectroscopy experiments, and ab initio quantum chemistry calculations. In each case, the water molecule inserts into the carbohydrate at a position where it can replace a weak intramolecular interaction by two stronger intermolecular hydrogen bonds. The insertion can produce significant changes in the conformational preferences of the carbohydrates, and there is a clear preference for structures where cooperative effects enhance the stability of the monosaccharide conformers to which the water molecule chooses to bind. The conclusions drawn from the study of monosaccharide-water complexes are extended to the disaccharide lactose and discussed in the light of the underlying mechanisms that may be involved in the binding of carbohydrate assemblies to proteins and the involvement, or not, of key structural water molecules.